Image of Health House in Indonesia Based on Susenas 2017 - Veridona, Ginoga; Prabawa, Artha (HIGIENE: Jurnal Kesehatan Lingkungan, 2020)
Houses are a primary need for humans. The need for houses that meet healthy requirements is very important in order to improve household health status and prevent disease. The parameters of a healthy house have been regulated by a law issued by the Ministry of Health where there are 17 parameters that must be met. The purpose of this paper is to know the overview of healthy houses in Indonesia. The data used is the 2017 Susenas module. The assessment of healthy houses is based on 17 parameters which are divided into three categories, namely good, medium and less. From the results of the analysis it was found that the number of healthy houses in Indonesia was 11.3% good / fulfilling healthy conditions, 75.70% moderate categories, and 13.00% less categories. The results of mapping the number of houses in good condition are mostly in Java, Bali and southern Sumatra. Keywords : house, healthy house, mapping